2009
DOI: 10.1136/qshc.2007.025742
|View full text |Cite
|
Sign up to set email alerts
|

Use of a risk analysis method to improve care management for outlying inpatients in a university hospital

Abstract: Using FMECA, we were able to identify the most critical failure modes of the complex process of care provided for outlying patients and to suggest subsequent improvement measures. Follow-up indicators were defined to assess implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…The findings of this study concord with a study that suggested that lack of input from specialist doctors and poor communication between wards may compromise safety,2 with studies that suggested the knowledge of nursing staff may be compromised,20–22 and with a study that suggested that having patients on inappropriate wards creates excess demand on physicians' time 5. Furthermore, the contributory factors identified in this study are easily encapsulated within frameworks which have been devised to investigate and analyse patient safety incidents in healthcare, for example, the London Protocol,31 and human factors frameworks 32.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The findings of this study concord with a study that suggested that lack of input from specialist doctors and poor communication between wards may compromise safety,2 with studies that suggested the knowledge of nursing staff may be compromised,20–22 and with a study that suggested that having patients on inappropriate wards creates excess demand on physicians' time 5. Furthermore, the contributory factors identified in this study are easily encapsulated within frameworks which have been devised to investigate and analyse patient safety incidents in healthcare, for example, the London Protocol,31 and human factors frameworks 32.…”
Section: Discussionsupporting
confidence: 76%
“…This phenomenon is also evident in other countries with publicly funded healthcare systems, including France,2 Spain3 and New Zealand 4 5. Such patients are commonly called ‘outliers’, ‘sleep outs’ or ‘boarders’.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Few studies have been undertaken of outlying patients [16-18]. There have been some studies highlighting the risk exposure of outlying patients but these only took into account paramedical care and only studied patients in surgery and traumatology [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…In the U.K., it has been shown that there is a lack of knowledge among nurses in medical wards about caring for surgical patients compared to nurses in orthopedic or traumatology wards [16,17]. A study in France has emphasized the need for designating a contact doctor in wards that have outlying patients in other wards, as well as a nursing care coordinator and making sure medical files are standardized throughout the hospital [18]. Previous studies only looked at medical care delivered by paramedics on surgical or traumatology patients and did not give any description of the outcomes of those patients [16,17].…”
Section: Introductionmentioning
confidence: 99%